Suitability estimation of some bioengineered grass species in terms of their root reinforcement ability, conservation and forage value under various landslide prone hill forest of Darjeeling Himalaya - Misra, T.K.; Bhutia, T.T.; Biswas, R.; Mandal, P. (Indian Forester, 2022)
The study deals with the quantitative evaluation of twelve different bioengineered grass species for their root reinforcement ability, conservation values and forage values. Erodibility factor was also determined for forecasting occurrence of landslide in five different places of Darjeeling. Among these, Upper Mahanadi (0.110) and West Balason (0.109) Catchment Range area were found to be very high landslide prone. Vetiveria zizanioides was ranked first among the twelve grass species for having the highest soil binding strength index, shear tensile strength, conservation value, cohesion value and least acceptable to the wild and livestock animals; whereas Themeda arundinacea showed better soil binding abilities as compared to other grass species in all respect. Grass roots provide natural reinforcement to the mechanical structures like gully control, runoff disposal and stream bank control etc. and can give better stabilization and effective protection as well as they can also be used for green fodder.